Changes in retinal ischaemic index correlate with recalcitrant macular oedema in retinal vein occlusion: WAVE study. Issue 8 (26th April 2018) - Kwon, Soonil; Wykoff, Charles Clifton; Brown, David M; van Hemert, Jano; Fan, Wenying; Sadda, SriniVas R
Abstract : Aim: To evaluate changes in the ischaemic index (ISI) after targeted retinal photocoagulation (TRP) and to investigate the correlation between these changes and macular oedema (ME). Method: Twenty-four eyes of 24 patients with retinal vein occlusion (RVO) with recurrent ME were included. Ultra-widefield fluorescein angiography (UWFFA; Optos 200Tx) was obtained at baseline and every 4 months. The regions of retinal non-perfusion and the total gradable retina were manually segmented on UWFFA images for calculating the global ISI. ISI was also computed for specific regions defined by a standardised grid: perimacular area (PMA), near-peripheral area (NPA), mid-peripheral area (MPA) and far-peripheral area (FPA). Global and regional ISIs and change in ISI over time were correlated with central macular thickness (CMT). Results: The ISIs of entire retina, PMA, NPA, MPA and FPA at baseline were 30.5%±23.3, 17.7%±20.6, 21.9%±19.0, 33.0%±27.9 and 48.0%±32.9, respectively. The ISIs at final follow-up were 23.5%±19.9, 15.7%±22.2, 16.5%±16.7, 24.7%±24.7 and 24.7%±24.7, respectively. A significant correlation was found between CMT and global ISI during follow-up (r=0.22, p=0.03). Among the different retinal zones, PMA showed a correlation with CMT (r=0.27, p=0.007). The change in ISI for the total retina (Δtotal), PMA (ΔPMA) and NPA (ΔNPA) retinal regions was positively correlated with the change in CMT (ΔCMT) (r=0.45, 0.42 and 0.50, respectively, p=0.006, 0.009 and 0.002, respectively). Conclusion: The severity of ME was correlated with the ISIs of the entire retina and the PMA. The reduction in ME was correlated with the reduction in ISI of the entire retina as well as the ISIs for the NPA and PMA following TRP. The role of TRP, particularly to these regions (NPA, PMA), warrants further investigation in recalcitrant RVO-associated ME.